2022
DOI: 10.3390/jcm11195636
|View full text |Cite
|
Sign up to set email alerts
|

Increased Macrophage-like Cell Density in Retinal Vein Occlusion as Characterized by en Face Optical Coherence Tomography

Abstract: Objectives: to quantitatively analyze macrophage-like cells (MLCs) at the vitreoretinal interface in retinal vein occlusion (RVO) using swept-source optical coherence tomography angiography (SS-OCTA) and en face optical coherence tomography (OCT). Methods: The study included 72 RVO patients, with 43 acute patients and 29 chronic patients. For a normal control, 64 fellow eyes were included. MLCs were visualized in a 5 μm en face OCT slab above the vitreoretinal interface centered on the fovea. After semi-automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Since PDR shares many pathophysiologic features with RVO, including ischemia and inflammation, we hypothesized that MLCs are more numerous in RVO eyes. In agreement, Zeng et al and Wang et al recently showed that MLC density was significantly increased in RVO eyes [ 21 , 22 ]. However, Zeng et al did not investigate if MLCs can predict meaningful RVO outcomes.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Since PDR shares many pathophysiologic features with RVO, including ischemia and inflammation, we hypothesized that MLCs are more numerous in RVO eyes. In agreement, Zeng et al and Wang et al recently showed that MLC density was significantly increased in RVO eyes [ 21 , 22 ]. However, Zeng et al did not investigate if MLCs can predict meaningful RVO outcomes.…”
Section: Introductionsupporting
confidence: 82%
“…However, Zeng et al did find that MLC density significantly correlated with increased macular thickness, which we did not observe [ 21 ]. Similarly, Wang et al observed a positive correlation between MLC density and macular thickness in chronic eyes, but a negative association in acute eyes [ 22 ]. Since our study investigated a cross-sectional population including both acute and chronic eyes, we did not find an association between MLCs and baseline CST because the acute and chronic patients have inverse associations, canceling out each another.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the current study, our finding, that MLC density increased a lot in eyes with DME, is consistent with previous experimental results and provide clinical evidence that macrophage/microglia may participate in DME pathological process. Our previous study in retinal vein occlusion also showed that MLC density correlated positively with retina thickness in chronic patients [ 19 ]. Another interesting result is that the positive correlation between MLC density and retinal thickness was established only in NPDR group.…”
Section: Discussionmentioning
confidence: 84%
“… 44 47 Putative retinal gliosis (activated retinal astrocytes, microglia, and Müller cells) has been quantitatively characterized as hyper-reflective patches on SD-OCT en face images that correspond to similar structures on the b-scans in glaucoma, 45 , 48 50 diabetic retinopathy, 51 53 and retinal vein occlusion. 54 The presence of these hyper-reflective structures (putative gliotic changes) and the extent of retinal region covered with them have been reported to have a greater potential of being an indicator for glaucomatous degeneration. 45 These areas of putative gliosis are also increased in proliferative diabetic retinopathy compared to nonproliferative and control participants, with patients with diabetic macular edema having larger areas compared to patients with no macular edema.…”
mentioning
confidence: 99%